Avaliação da citotoxicidade de biomaterial ósseo descelularizado - Favalessa, Affonso Martinho Burini Bortolotti (2023)
The regeneration of bone defects of different origins is still a challenge in the medical and dental fields. Currently, numerous bone substitutes are used in grafting procedures resulting from injuries or trauma. However, only a few manage to promote biochemical interactions with the body, being the targets of research in bone tissue regeneration. Therefore, tissue bioengineering is responsible for evaluating the capacity for osseointegration, a direct interaction between the bone and the implanted biomaterial, which promotes rapid adhesion and higher quality in the procedure. Results of previous research from the Tissue Biotechnology Center have shown to produce a decellularized scaffold from fetal bone tissue with morphological characteristics ideal to be a new and promising bone biomaterial. Continuing the research, this project aims to evaluate the cytotoxicity of the biomaterial when in contact with mesenchymal stem cells (MSC). The decellularization of fetal bone biomaterial of bovine origin was performed and then the value of residual DNA and SDS, elemental composition and cytotoxicity test with human cells derived from adipose tissue stromal mesenchyme were analyzed. Finally, this study evaluated the bone scaffolds developed in this study showed low biocompatibility in vitro, demonstrating the low adhesion of the cells to the material.